Correlation effects in two-dimensional MX2 and MA2Z4 (M = Nb, Ta; X = S, Se, Te; A = Si, Ge; Z = N, P) cold metals: Implications for device applications - Beida, W.; Sasioglu, E.; Tas, M.; Friedrich, C.; Bluegel, S.; Mertig, I.; Galanakis, I. (Amer Physical Soc, 2025)
Cold metals, characterized by their distinctive band structures, hold promise for innovative electronic devices such as tunnel diodes with negative differential resistance (NDR) effect and field-effect transistors (FETs) with sub-60 mV/dec subthreshold swing (SS). In this study, we employ the GW approximation and HSE06 hybrid functional to investigate the correlation effects on the electronic band structure of two-dimensional cold metallic materials, specifically focusing on MX2 and MA2Z4 (M = Nb, Ta; X = S, Se, Te; A = Si, Ge; Z = N, P) compounds in 1H structure. These materials exhibit a unique band structure with an isolated metallic band around the Fermi energy, denoted as Wm, as well as two energy gaps: the internal gap EgI below the Fermi level and the external gap EgE above the Fermi level. These three electronic structure parameters play a decisive role in determining the current-voltage (I-V ) characteristics of tunnel diodes, the nature of the NDR effect, and the transfer characteristics and SS value of FETs. Our calculations reveal that both GW and HSE06 methods yield consistent electronic structure properties for all studied compounds. We observed a consistent increase in both internal and external band gaps, as well as metallic bandwidths, across all pn-type cold metal systems. Notably, the internal band gap EgI exhibits the most substantial enhancement, highlighting the sensitivity of these materials to correlation effects. In contrast, the changes in the metallic bandwidth Wm and external band gap EgE are relatively modest. These findings offer valuable insights for designing and optimizing cold metal-based devices. Materials like NbSi2N4, NbGe2N4, and TaSi2N4 show particular promise for high-performance NDR tunnel diodes and sub-60 mV/dec SS FETs.
Keywords: Band-Tails; Approximation